Experiences in Managing Public Assets of Public Higher Education Institutions in Some Countries in the World and Lessons Learned for Vietnam - huy, Nguyen Thanh (Business and Economic Research, 2024)
Public asset management plays a crucial role in ensuring the efficient use of public resources and promoting transparency in government operations. Proper management of public assets, such as land, buildings, and infrastructure, helps optimize their value, reduces waste, and supports sustainable development. In the context of higher education institutions, effective asset management not only ensures that resources are used efficiently to improve facilities and services but also contributes to the long-term financial stability of the institution. By adopting sound asset management practices, governments can enhance public trust, ensure accountability, and better meet the needs of society. This paper explores the management of public assets in public education institutions across several countries and draws lessons for Vietnam. By analyzing asset management practices in countries such as China, Australia, and Canada, this paper identifies key strategies that contribute to efficient resource utilization in public education institutions. The paper further emphasizes the necessity for Vietnam to adapt these international best practices to its own context.